Saturday

March 28, 2015

March 28, 2015

Posted by **Matt** on Sunday, October 7, 2007 at 10:43pm.

I got

1

=======================

|x+3|sqrt(x+3)^(2)-1

Is this the final answer or do you need to solve (x+3)^2 and get (x^(2) + 9x + 9)

- Calculus Verification -
**drwls**, Sunday, October 7, 2007 at 10:58pmThe answer is

1

--------------------

(x+3)sqrt[(x+3)^2 -1]

Your answer should not have absolute value | | symbols around x+3, and needs brackets around (x+3)^2 -1, to show that you take the square root of everything in brackets.

**Answer this Question**

**Related Questions**

Calculus AB - I'm trying to find the second derivative of h(x)= x^2 + cos(kx) My...

Calc I - if f(t)=sqrt(4t+1) find f''(2) I got the first derivative to be: 1/2(4t...

Calculus (Help) - Also I would like to know how to set this problem up in ...

Calculus - Find the derivative of cos(sqrt(e^(x^3)cos(x)) I got -sin(sqrt(e^(x^3...

calculus - Find the first and second derivative - simplify your answer. y=x/4x+1...

calculus - The question I'm having problems with is If f(x)=3x^2+7x+2, find f'(4...

Calculus Please Help - I think I have the right answer, but I am not 100% sure ...

Calculus - I've been trying to solve the improper integral of ln(x)/sqrt(x) dx ...

derivative am i right or wrong - what is the antiderivative of 1/(x^2-2x+2)? ...

Calculus - repost - Find the derivative of F(x)= integral from -2 to x of sqrt(t...